Personelle Ausstattung und Versorgungsqualität in bayerischen Alten- und Pflegeheimen : Bestandsaufnahme, Literaturüberblick und Feldstudie zu den Auswirkungen unterschiedlicher Leitungsmodelle auf die Versorgungsqualität - Lang, Frieder; Rupprecht, Roland; Engel, Sabine; Beyer, Anja; Kraus, Bertram; Liebich, Corinna; Volland-Schüssel, Käte; Sonnenberg, Magdalene (2009)

What are the Motives, Barriers and Support Requirements with regard to Weight Loss in Old Age? - Goerlitz, A.; Koching, M.; Torbahn, G.; Schöne, Daniel; Volland-Schüssel, Käte; Volkert, Dorothee; Kiesswetter, Eva (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Wishes of nursing home residents for their dying - Kurkowski, Sandra; Heckel, Maria; Volland-Schüssel, Käte (Zeitschrift für Gerontologie und Geriatrie, 2018)
BACKGROUND: Institutions of inpatient geriatric care are dependent on specific and practicable concepts for the terminal care of old people, because residential and nursing homes are places for the last phase of life. OBJECTIVE: The objective of this study was to identify the wishes of residents for their dying who live in a residential or nursing home. METHOD: The analysis was based on 10 semi-structured expert interviews with residential and nursing home residents. The interviews were evaluated using the method of qualitative summarizing content analysis. Based on the grounded theory a procedure was selected in which data were collected, prepared and evaluated in parallel. RESULTS AND DISCUSSION: Residents expressed, inter alia, the following wishes: not to receive life-prolonging measures, not to have pain, not to be in need of care or bedridden, to receive affection while dying and to find forgiveness and reconciliation as well as to die peacefully in the residential and/or nursing home. In addition, there were a variety of wishes, which, due to their diversity make a unified approach to the palliative care of older people in residential and/or nursing homes impractical. The study showed that residents are thinking about dying and/or death, have desires for their dying and are also willing to talk about it. The recording and the translation of these wishes and also the response to the residents' fears can be achieved by the implementation of a palliative culture and the training of employees.
EVALuna2:204778